Closed reduction in the treatment of neglected mandibular fractures at the Department of Oral and Maxillofacial Surgery, Universitas Airlangga - Olivia Jennifer Gunardi; Riska Diana; David Buntoro Kamadjaja; Ni Putu Mira Sumarta (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: The mandible is one of the bones most affected by facial fractures commonly resulting from trauma to the face. The ultimate goal of treatment is to re-establish the pre-injury dental occlusion (bite), mandibular anatomy and jaw function of the patient. Treatment approaches range from conservative non-invasive management by ’closed’ reduction and immobilization using intermaxillary fixation (IMF) to the more invasive surgery-based ’open’ reduction incorporating an internal fixation approach. Purpose: The purpose of this case series was to describe the close reduction method as a form of treatment in cases of neglected mandibular fracture. Cases: Four cases of single or multiple mandibular fracture were presented. Case management: All of the cases were managed using a closed reduction method and IMF. Conclusion: A closed reduction method in this case series produced encouraging results and could be considered an alternative in the treatment of neglected mandibular fractures with displacement.